Restructuring of Problematic Financing at BMT UGT Kalibaru and Its Impact on Financial Circulation - Ghofur, Rouf Abdul; Annas, Muhamad (Jurnal Maksipreneur, 2025)
Baitul Maal wa Tamwil serves as a representation of Islamic financial institutions established by government entities to foster and develop a banking framework that aligns with the principles of Islamic doctrine. One of its leading products is Islamic financing. Behind the scenes, financing restructuring often occurs due to problems. This study focuses on BMT UGT Kalibaru in handling financing cases. This study aims to 1) analyze the causes of problematic financing, 2) examine the stages of resolution used by BMT UGT Kalibaru in handling problematic financing cases, and 3) determine the impacts caused and their solutions. This type of research is a case study. The data sources used are primary and secondary data. Data collection techniques use documentation, archival recordings, interviews, and observations. Data analysis uses an interactive model. The results of this study state that: 1) the causes of problematic financing in general are two causes, namely internal and external causes, and 2) the stages of resolving problematic financing in general are two paths, namely litigation and non-litigation. The mechanism carried out by BMT UGT Kalibaru starts from the rescheduling stage, re-requirements, collateral deliberation, and collateral confiscation, 3) the impact of problematic financing results in members being unable to withdraw savings and the state of financial circulation in the office.